2005
DOI: 10.1111/j.1365-2044.2004.04073.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric characteristics of simulation‐based assessment in anaesthesia and accuracy of self‐assessed scores*

Abstract: SummaryThe purpose of this study was to define the psychometric properties of a simulation-based assessment of anaesthetists. Twenty-one anaesthetic trainees took part in three highly standardised simulations of anaesthetic emergencies. Scenarios were videotaped and rated independently by four judges. Trainees also assessed their own performance in the simulations. Results were analysed using generalisability theory to determine the influence of subject, case and judge on the variance in judges' scores and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
0
42
0
3
Order By: Relevance
“…The fact that many participants successfully avoided most of the errors suggests that few individual aspects of the simulations were unreasonably challenging. The engagement of participants was palpably genuine and they rated the simulations highly for realism, but we acknowledge limitations to this realism [31]. We think fidelity is critical to research involving immersion simulation, and that there is room for improvement in currently available simulators, but we believe we have paid as much attention to detail as we could (for example by using real drugs).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fact that many participants successfully avoided most of the errors suggests that few individual aspects of the simulations were unreasonably challenging. The engagement of participants was palpably genuine and they rated the simulations highly for realism, but we acknowledge limitations to this realism [31]. We think fidelity is critical to research involving immersion simulation, and that there is room for improvement in currently available simulators, but we believe we have paid as much attention to detail as we could (for example by using real drugs).…”
Section: Discussionmentioning
confidence: 97%
“…Simulation can potentially be used to assess anaesthetic practice or equipment [26][27][28][29][30][31][32]. The CPS has a number of advantages over the clinical setting for the study of human error.…”
mentioning
confidence: 99%
“…Residents in the upper quartile of performance underestimated their performance in additional specific competencies, whereas residents in the lowest performance quartile overestimated professionalism skills. A similar study in anesthesia residents demonstrated moderate correlation between self-and observer assessments when reviewing their performance on three emergency HFS scenarios; however, this correlation was poorer at the lower levels of performance, 97 further supporting the unreliability of self-assessment for patient care competence.…”
Section: Overview Of Assessment Methods Identifiedmentioning
confidence: 96%
“…Weller and colleagues revealed that anesthesiology residents' self-ratings of simulation-based performance modestly correlated with those of external assessors and that lower-scoring residents overrated their performance compared to higher-scoring residents (5). MacDonald showed, in a cohort of medical students performing technical skills, that with repetitive self-assessment, accuracy of self-assessment increased (6).…”
Section: Introductionmentioning
confidence: 96%